Mitochondrial modulation by Epigallocatechin 3-Gallate ameliorates cisplatin induced renal injury through decreasing oxidative/nitrative stress, inflammation and NF-kB in mice. - Hao Pan; Jun Chen; Kezhen Shen; Xueping Wang; Ping Wang; Guanghou Fu; Hongzhou Meng; Yimin Wang; Baiye Jin (PLoS ONE, 2015)
Cancer chemotherapy drug cisplatin is known for its nephrotoxicity. The aim of this study is to investigate whether Epigallocatechin 3-Gallate (EGCG) can reduce cisplatin mediated side effect in kidney and to understand its mechanism of protection against tissue injury. We used a well-established 3-day cisplatin induced nephrotoxicity mice model where EGCG were administered. EGCG is a major active compound in Green Tea and have strong anti-oxidant and anti-inflammatory properties. EGCG protected against cisplatin induced renal dysfunction as measured by serum creatinine and blood urea nitrogen (BUN). EGCG improved cisplatin induced kidney structural damages such as tubular dilatation, cast formation, granulovaculoar degeneration and tubular cell necrosis as evident by PAS staining. Cisplatin induced kidney specific mitochondrial oxidative stress, impaired activities of mitochondrial electron transport chain enzyme complexes, impaired anti-oxidant defense enzyme activities such as glutathione peroxidase (GPX) and manganese superoxide dismutase (MnSOD) in mitochondria, inflammation (tumor necrosis factor α and interleukin 1β), increased accumulation of NF-κB in nuclear fraction, p53 induction, and apoptotic cell death (caspase 3 activity and DNA fragmentation). Treatment of mice with EGCG markedly attenuated cisplatin induced mitochondrial oxidative/nitrative stress, mitochondrial damages to electron transport chain activities and antioxidant defense enzyme activities in mitochondria. These mitochondrial modulations by EGCG led to protection mechanism against cisplatin induced inflammation and apoptotic cell death in mice kidney. As a result, EGCG improved renal function in cisplatin mediated kidney damage. In addition to that, EGCG attenuated cisplatin induced apoptotic cell death and mitochondrial reactive oxygen species (ROS) generation in human kidney tubular cell line HK-2. Thus, our data suggest that EGCG may represent new promising adjunct candidate for cisplatin.